Teacher Education Program Contribution to Ensuring Appropriate Practice at Preprimary Schools of Ethiopia - Gedefa, Walelign Admasu; Mehirete, Dawit Mekonnen (Universitas Negeri Semarang, 2023)
Teacher education programs are essential components in providing quality education for children. This study attempted to explore the contribution of Teacher Education programs in acquainting preprimary school teachers with the guiding principles, relevant curriculum, the learning cycles of children, and fit instruction and assessment methods for children in practicing curricular activities at preprimary schools. A descriptive survey approach was used in the study. Data were collected from 221 randomly selected graduating class trainees and five purposively selected trainers using questionnaires, interviews, and discussions. The data were analyzed using frequency, percentage, and thematic analysis, and qualitative data were summarized using the following logic. High percentages of respondents did not favor the contribution of Teacher Education programs in acquainting trainees with the guiding principles of child development and learning, appropriateness of the curriculum, learning cycles of children, practice of relevant curricular activities, application of fit methods of instruction and assessment means for children at the expected levels. Besides, problems were reported in teacher education programs, such as unsuitable materials, challenging courses, negative attitudes toward the profession, time shortages, and the absence of centers for skill development. Parallel measures to be taken to alleviate the problems were suggested. Thus, the study has its benefits in indicating the limitations of the teacher education program to take measures in the future at preprimary schools in Ethiopia and the world at large.